Pediatric Critical Care in Resource Limited Settings—Lessening the Gap Through Ongoing Collaboration, Advancement in Research and Technological Innovations - Bjorklund, Ashley; Slusher, Tina; Day, Louise Tina; Yola, Mariya Mukhtar; Sleeth, Clark; Kiragu, Andrew; Shirk, Arianna; Krohn, Kristina; Opoka, Robert (Frontiers in Pediatrics, 2022)
Pediatric critical care has continued to advance since our last article, “Pediatric Critical Care in Resource-Limited Settings – Overview and Lessons Learned” was written just three years ago. In that article, we reviewed the history, current state, and gaps in level of care between low- and middle-income countries (LMICs) and high-income countries (HICs). In this article, we have highlighted recent advancements in pediatric critical care in LMICs in the areas of research, training and education, and technology. We acknowledge how the COVID-19 pandemic has contributed to increasing the speed of some developments. We discuss the advancements, some lessons learned, as well as the ongoing gaps that need to be addressed in the coming decade. Continued understanding of the importance of equitable sustainable partnerships in the bidirectional exchange of knowledge and collaboration in all advancement efforts (research, technology, etc.) remains essential to guide all of us to new frontiers in pediatric critical care.